HSP90 IN CANCER: TRANSCRIPTIONAL ROLES IN THE NUCLEUS - Calderwood, S. K. (Adv Cancer Res, 2015)
Hsp90 plays a key role in fostering metabolic pathways essential in tumorigenesis through its functions as a molecular chaperone. Multiple oncogenic factors in the membrane and cytoplasm are thus protected from degradation and destruction. Here we have considered Hsp90’s role in transcription in the nucleus. Hsp90 functions both in regulating the activity of sequence specific transcription factors such as nuclear receptors and HSF1, as well as impacting more globally acting factors that act on chromatin and RNA polymerase II. Hsp90 influences transcription by modulating histone modification mediated by its clients SMYD3 and trithorax / MLL, as well as by regulating the processivity of RNA polymerase II through negative elongation factor (NELF). It is not currently clear how the transcriptional role of Hsp90 may be influenced by the cancer milieu although recently discovered posttranslational modification of the chaperone may be involved. Dysregulation of Hsp90 may thus influence malignant processes both by modulating the function of specific transcription factors and effects on more globally acting general components of the transcriptional machinery.